2015
DOI: 10.1007/7854_2015_416
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Toxic Insults and Onset of Sporadic Neurodegenerative Diseases—an Overview of Experimental Studies

Abstract: The developmental origin of health and disease hypothesis states that adverse fetal and early childhood exposures can predispose to obesity, cardiovascular, and neurodegenerative diseases (NDDs) in adult life. Early exposure to environmental chemicals interferes with developmental programming and induces subclinical alterations that may hesitate in pathophysiology and behavioral deficits at a later life stage. The mechanisms by which perinatal insults lead to altered programming and to disease later in life ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 142 publications
5
24
0
Order By: Relevance
“…It was shown that microglia of adult rats exposed to E. coli bacteria in the neonatal period had a stronger response to a secondary LPS challenge compared to naïve rats' microglia. [79][80][81] In all, 102 identical DMRs were identified between P4 and P24 for which half preserved their methylation status and the other half shifted to the opposite status. 73 Indeed, the methylation alterations in inflammatory pathways seen in this study could be a key component of a chronic low-level inflammation state, which is being increasingly recognized as central to cognitive decline, neuropsychiatric, and neurodegenerative diseases.…”
Section: F I G U R E 4 Methylation Levels Of Genes Of Interest Associmentioning
confidence: 98%
“…It was shown that microglia of adult rats exposed to E. coli bacteria in the neonatal period had a stronger response to a secondary LPS challenge compared to naïve rats' microglia. [79][80][81] In all, 102 identical DMRs were identified between P4 and P24 for which half preserved their methylation status and the other half shifted to the opposite status. 73 Indeed, the methylation alterations in inflammatory pathways seen in this study could be a key component of a chronic low-level inflammation state, which is being increasingly recognized as central to cognitive decline, neuropsychiatric, and neurodegenerative diseases.…”
Section: F I G U R E 4 Methylation Levels Of Genes Of Interest Associmentioning
confidence: 98%
“…Chronic inflammation and, in particular, MIA could be a major factor that contributes to the development of neurodegenerative disorders such as Alzheimer’s disease. 25 , 26 , 27 Lahiri et al 28 proposed a 'Latent Early-life Associated Regulation' model, postulating that latent changes in the expression of specific genes initially primed at the developmental stage of life. However, the involvement of microglia in neuropsychiatric diseases is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and clinical data support the hypothesis that inflammation itself might be a risk factor for neurodegeneration during AD (Ott et al, 1999;Bertram et al, 2007;Takahashi et al, 2007;Tartaglione et al, 2016). For instance, and Ling Z. D. et al (2004) exposed rats to LPS prenatally and then administered with a subtoxic dose of the dopaminergic (DA) neurotoxin rotenone (1.25 mg/kg per day for 14 days) when 16 months old.…”
Section: Maternal Programing By Exposure To High-fat-high-sugar Dietsmentioning
confidence: 89%